1994
DOI: 10.1086/174123
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical evidence for dark matter: X-ray constraints on the mass of the elliptical galaxy NGC 720

Abstract: We describe (1) a new test for dark matter and alternate theories of gravitation based on the relative geometries of the X-ray and optical surface brightness distributions and an assumed form for the potential of the optical light, (2) a technique to measure the shapes of the total gravitating matter and dark matter of an ellipsoidal system which is insensitive to the precise value of the temperature of the gas and to modest temperature gradients, and (3) a method to determine the ratio of dark mass to stellar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
152
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(160 citation statements)
references
References 49 publications
8
152
0
Order By: Relevance
“…A consequence of the pressure equilibrium is the X-ray shape theorem (Buote & Canizares 1994, i.e. the gas in strict hydrostatic equilibrium follows the iso-potential surfaces of the underlying matter distribution.…”
Section: Gas Shapementioning
confidence: 99%
See 1 more Smart Citation
“…A consequence of the pressure equilibrium is the X-ray shape theorem (Buote & Canizares 1994, i.e. the gas in strict hydrostatic equilibrium follows the iso-potential surfaces of the underlying matter distribution.…”
Section: Gas Shapementioning
confidence: 99%
“…The black lines shows the marginalised a-priori distributions under the q-flat prior. tial after projection in the hypothesis of spheroidal symmetry for the emitting system (Buote & Canizares 1994. Here, we can directly compare the axis ratios in three dimensions without restricting assumptions on the cluster shape.…”
Section: Gas Shapementioning
confidence: 99%
“…To reconcile these observations with the chemical enrichment models, it has been postulated that galaxy groups accrete primordial gas after they have been expelling gas during most of their evolution (Renzini 1997). Buote and Canizares (1994) showed that if a galaxy spectrum has intrinsically two temperature components, the single-temperature model can give a significantly underestimated metallicity. Buote (2000b) demonstrated that in a spectrum characterised by two temperatures, one below 1 keV and one above 1 keV, with an average of ∼1 keV, the lower temperature component preferentially excites emission lines in the Fe-L complex below 1 keV (Fe XVII-XXI), while the higher temperature component excites the Fe-L lines from ∼1-1.4 keV (Fe XXI-XXIV).…”
Section: Spectral Modelling and The Most Common Biasesmentioning
confidence: 99%
“…In both these regions the abundances were determined using only a one temperature collisional emission model (the ring model also included a power law component), and using low resolution ACIS spectra (compared to the Chandra gratings and XMM-Newton RGS). It has been shown that a one temperature collisional model at sub solar abundances and a two temperature collisional model at (or near) solar abundances cannot be distinguished at CCD resolution (Buote & Canizares 1994;Buote & Fabian 1998), and as the Wang et al (2009) study took place before the publication of any high resolution soft X-ray spectra of this object, we suspect this may be the case here. Without the resolution to determine the strengths of and ratios between individual emission lines, distinguishing the contribution of collisional and photoionised emission to the soft X-ray spectrum is subject to great uncertainties, and therefore we consider these abundances also to be uncertain.…”
Section: Higher Nitrogen Abundancesmentioning
confidence: 82%